Post-Occopancy Evaluation of Hasanuddin University Urban Park - Nadji, Etiwu; Radja, Abdul Mufti; Harisah, Afifah (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2023)
Urban Park is one of the public open spaces that play a role in preserving the environment. Hasanuddin University Urban Park is known as the lungs of Makassar City. The key of a public open space is influenced by a few ideal criterias based on the ideal criteria for public open space according to Kathleen Madden and the Project for Public Space used in this study, such as: (a) Sociability (social interaction that occurs); (b) Uses and activities; (c) Access and Linkages, and (d) Comfort and Image (a comfortable and interesting place to visit). This study aims to (1) Identify the condition of the Hasanuddin University Urban Park based on the ideal criterias for public open space according to Kathleen Madden and Project for Public Space; (2) Describe the influence of visitor behavior refer to the condition of Hasanuddin University Urban Park. This study uses a descriptive analysis methods and place centered mapping analysis methods, the data collection techniques is using data triangulation (observations, interviews, and secondary data). The result and discussion shows that the condition of the Hasanuddin University Urban Park refer to the ideal criteria for public open space according to Kathleen Madden and Project for Public Space, is some aspects of intangibles and aspects of measurements have not met the criteria. Visitor behavior that occurs in urban parks is influenced by the condition of existing park facilities and attributes such as visitor parking behavior, visitor environmental hygiene behavior and visitor alert behavior. Keywords: Evaluation of post-occupancy; ideal criteria for public open space; urban parks; visitor behavior.